Nilai Kepimpinan Islam dalam Kerajaan Uthmaniyah: Analisis terhadap Empat Pemimpin Utama Pada Era Awal: The Values of Islamic Leadership in the Ottoman Empire: An Analysis of the Four Early Leaders - Ainur Mardhiah Mazlan; Ibrahim, Muhammad Khalis (Journal Al-Muqaddimah, 2025)
At a time when the Muslim world is facing a leadership crisis, the early history of the Ottoman Empire offers an opportunity for reflection on how Islamic leadership values were able to shape a great civilization that successfully ruled over three continents for more than six centuries. Although the early history of the Ottoman Empire has been widely discussed, most studies have focused primarily on political, military, and territorial aspects, while the dimension of Islamic leadership values, which in fact served as the foundation of the empire’s strength and longevity, has received relatively little holistic attention. Therefore, this article aims to analyze the Islamic leadership values practiced by the early Ottoman leaders and to assess their relevance to contemporary Muslim leadership. This qualitative study is based on a comparative analysis of four prominent leaders of the early Ottoman period, namely Osman I, Sultan Mehmed II, Sultan Selim I, and Sultan Suleiman I. The findings reveal that leadership values were a decisive factor in the success of Ottoman Empire during its early period. These values not only strengthened the empire’s military power and political authority but also fostered a people-friendly administration respected by other contemporary states. This study contributes to contemporary discourse on the leadership crisis in the Muslim world by offering the Ottoman leadership model as a relevant example and reference for reviving the spirit and values of capable leadership among the younger Muslim generation.